Revealing the Spirit of Place: The Former Campus of the Indonesian Academy of Fine Arts in Yogyakarta - Raden Bagus Budho Diwangkoro; Aditya Noor Hadhy Utama; Putu Ayu Pramanasari Agustiananda; Arif Budi Sholihah (Universitas Teknologi Yogyakarta, Yogyakarta, Indonesia, 2025)
In many urban heritage contexts, adaptive reuse often prioritizes physical and economic transformation while neglecting the intangible dimensions that shape a site’s identity. The former campus of the Indonesian Academy of Fine Arts (ASRI) in Yogyakarta, that now revitalized as the Jogja National Museum (JNM) and JNM Bloc, is a compelling case to examine how the spirit of place (genius loci) evolves in response to cultural, spatial, and functional shifts. This study aims to analyze the historical transformation and adaptive reuse of the ASRI campus and to explore the persistence or redefinition of its genius loci through the dimensions of image, space, and character. Employing a qualitative case study design, data were collected through field observations, semi-structured interviews with stakeholders (including alumni, artists, and museum managers), and archival documentation. Data were analyzed using phenomenological interpretation, focusing on the relationships between tangible heritage, community memory, and symbolic meaning. The results show that despite commercial insertions and spatial reprogramming, the site retains its identity as an arts and cultural landmark. Key findings include the role of community actors in preserving memory, the hybridization of academic and public spaces, and the use of symbolic anchors (e.g., banyan tree, monuments) to sustain continuity. This study contributes conceptually to adaptive reuse discourse by proposing an integrated framework that links spatial adaptation with cultural memory. However, the study is limited by its single-site focus and scope of informants. Future studies are encouraged to explore comparative analyses of other culturally transformed heritage sites to gain deeper insights into experiential authenticity and the construction of place identity.